The average rate of change is 12.
27 - 3 = 24.
1 - (-1) = 2 [it’s essentially 1 + 1].
24/2 = 12.
Answer:
A) 2k+4
Step-by-step explanation:
To solve for terms of x, we need to. she sure that x is on its own side while every other term is on the other side.
To start, we will cross multiply. If we have a/b=c/d, then ad=bc
We can perform the same calculation here,
6/x=3/(k+2)
6(k+2)=3x
Divide both sides by 3
2(k+2)=x
x=2k+4
I would say no it’s not correct, the point is not in the correct place
Answer is <span>16y + 7z
</span><span><span><span><span>9y</span>+<span>11z</span></span>+<span>7y</span></span>−<span>4z
</span></span><span>=<span><span><span><span><span>9y</span>+<span>11z</span></span>+<span>7y</span></span>+</span>−<span>4z
</span></span></span>Combine Like Terms:
<span>=<span><span><span><span>9y</span>+<span>11z</span></span>+<span>7y</span></span>+<span>−<span>4z
</span></span></span></span><span>=<span><span>(<span><span>9y</span>+<span>7y</span></span>)</span>+<span>(<span><span>11z</span>+<span>−<span>4z</span></span></span>)
</span></span></span><span>=<span><span>16y</span>+<span>7z</span></span></span><span>
</span>